2015
DOI: 10.5005/jp-journals-10024-1725
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Orthodontic Tooth Movement in Gingival Crevicular Fluid: A Systematic Review

Abstract: Background The analysis of gingival crevicular fluid (GCF) may be an acceptable way to examine the ongoing biochemical processes associated with bone turnover during orthodontic tooth movement. If it is possible to biologically monitor and predict the outcome of orthodontic forces, then the management of appliances could be based on individual tissue responses, and the effectiveness of the treatment could be improved. Methodology A literature search was carried out in major databases, such as medline, EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 87 publications
1
36
1
2
Order By: Relevance
“…10,24 While GCF volumes did not differ between or within test sites and control sites as previously described in the literature, 13 interestingly, a significant increase of IL-1b in the GCF samples of test teeth with respect to those obtained from the control teeth was observed in this study. Furthermore, when considering GCF samples obtained from pressure and tension sites, an increased level of 1b was evident at the pressure sites.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…10,24 While GCF volumes did not differ between or within test sites and control sites as previously described in the literature, 13 interestingly, a significant increase of IL-1b in the GCF samples of test teeth with respect to those obtained from the control teeth was observed in this study. Furthermore, when considering GCF samples obtained from pressure and tension sites, an increased level of 1b was evident at the pressure sites.…”
Section: Discussionsupporting
confidence: 80%
“…3,6 TGF-1b is one of the key cytokines with pleiotropic properties that has both proinflammatory and antiinflammatory features in the regulation of the inflammatory infiltrate. 24 After 3 weeks of aligner therapy, our results showed an increased level of this cytokine at the tension sites of the test teeth. TGF-1b plays a role in bone destruction; however, an increased concentration of this marker has been demonstrated at both tension and compression sites, revealing a complex role of this mediator.…”
Section: Discussionmentioning
confidence: 61%
“…3 The GCF analysis may provide a noninvasive method to investigate the biochemical changes and cellular response of the underlying periodontal ligament during orthodontic movement. 4,7 Studies have confirmed that both RANKL and OPG can be detected in human GCF during orthodontic movement. [8][9][10] The methods of orthodontic treatment mechanics have been developed throughout orthodontics history to complement clinicians achieving the desired result on various orthodontic cases.…”
Section: Introductionmentioning
confidence: 90%
“…Mechanical loading also alters periodontal tissue vascularity, metabolic process and blood flow resulting in the local synthesis and release of various molecules such as arachidonic acid, cytokines, growth factor, and colony-stimulating factors until tooth movement occurs. 7 The released molecules as cellular responses in the various cell types in and around teeth, such as fibroblasts, osteoblasts, cementoblasts, and vascular cells as a stressor response of mechanical forces, provide a favourable microenvironment for tissue apposition or resorption in orthodontic tooth movement. 3 When orthodontic forces are applied to the tooth, the resulting pressure will induce fibroblast cells, osteoclasts and osteoblas in periodontal ligament as a response to mechanical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…8 Extracellular changes and crevicular gingival fluid as a biomarker orthodontic response occured. 7 Collagen became the most important tissue in periodontal ligament remodeling. The ligament itself undergoes remodeling and the role of MMPs with their natural inhibitors, tissue inhibitors of metalloproteinases (TIMPs), are clearly of importance.…”
Section: Introductionmentioning
confidence: 99%